Necriphysiphilia as a psychopathology of the anthropocene epoch and, a dissoanalytic political psychology perspective on the transformation of individual trauma to social trauma - Erdinc Ozturk (Medicine Science, 2024)
In today's Anthropocene Epoch, human-induced individual traumas are rapidly transforming into human-induced societal traumas, and vice versa. The Anthropocene Epoch has created "dystopian societies" characterized by "uncertainty traumas", "uncertainty anxieties", and "epidemic traumas" which have pluralized individuals' identities, consciousness, and memories, even locking them into a submissive psychosocial mode! As a psychopathology of the Anthropocene Epoch, necriphysiphilia is characterized by postmodern primitive relationships and fusioned lifestyles defined by dependencies on pleasure, technology, and luxury. From a dissoanalytic school perspective, necriphysiphilists are individuals lacking social missions, obsessed with luxury brands, possessing low intellectual levels, and indulging in vacation and entertainment, who have established "dissociative identifications" with their own abusers, while being hostile to nature. Necriphysiphiliacs appease their ideals of living under autocratic regimes by submitting to their dominant partners and leaders, often at the cost of their own freedoms. For dissociated subjects and societies, the "last exit before the bridge" involves safe habitats that are intertwined with nature, amidst environmental destruction, urban sprawl, epidemic traumas, multiple dependencies, and ongoing oppression. The recent strong trend toward eco-friendly habitats serves as a robust manifesto against educational abuse, scientific tyranny, academic mobbing, and necriphysiphilia. Within this manifesto, Ozturk's "Dissoanalytic Political Psychology" analyzes necriphysiphiliacs -who sacrifice their freedoms for pleasure, interests, and luxury- through the lens of "dysfunctional mass psychology". Dissoanalytic political psychology is a field that examines the psychosocial origins and reflections of human thought, emotion, and behavior in political life through the framework of "dissoanalysis theory". According to this theory, dissociative revolutions against political traumas and political dissociation enable the long-term prevalence of peace-focused, empathetic, sensible, just, and meritocratic societies. [Med-Science 2024; 13(4.000): 962-72]